FSTL1 promotes dendritic cell pyroptosis and immunosuppression in sepsis by inhibiting STING autophagy - Qiong Li; Hua Ling; Jingyi Li; Jinru Li; Wentao Duan; Lijun Guo; Xingui Dai (PLoS ONE, 2026)
Background Sepsis-induced immunosuppression, characterized by dendritic cell (DC) depletion, correlates with poor outcomes. The glycoprotein FSTL1 is elevated in sepsis, but its contribution to DC pyroptosis and subsequent immune dysfunction remains unknown. Methods We utilized in vitro models with splenic DCs and mouse dendritic cell line DC2.4, alongside a murine cecal ligation and puncture (cecal ligation and puncture) sepsis model. The roles of STING and autophagy were probed using specific modulators (STING agonist DMXAA; STING specific inhibitor C-176; autophagy inhibitor 3-methyladenine). Pyroptosis was assessed by quantifying cleaved CASP1 and GSDMD-N via Western blotting and flow cytometry. STING pathway activation and autophagic flux were evaluated by detecting protein phosphorylation (p-STING, p-TBK1) and key markers (LC3B, P62) through Western blotting, immunofluorescence, and co-immunoprecipitation. DC-mediated T-cell responses were determined by proliferation assays and cytokine secretion analysis. Results FSTL1 was found elevated and correlated withDC pyroptosis in vitro and in septic mice. Mechanistically, FSTL1 inhibited the autophagic degradation of STING, leading to its accumulation and subsequent activation. Consequently, this impaired T-cell priming capacity and resulted in immunosuppression in vivo . Inhibition of STING attenuated FSTL1-induced pyroptosis, restored DC-mediated T-cell activation, and ameliorated immunosuppression. In murine septic models, FSTL1 exacerbated multiple organ injury and increased mortality, effects that were reversed by STING inhibition. Conclusion Our findings demonstrate that FSTL1 correlates with impaired STING autophagic degradation and DC pyroptosis, suggesting a potential pathway contributing to septic immune dysfunction.